A nurse‐led, rheumatologist‐assisted telemedicine intervention for dose escalation of urate‐lowering therapy in gout. (1st June 2020) - Phang, Kee Fong; Santosa, Amelia; Low, Bernadette P. L.; Tan, Pamela S. H.; Khong, Zhi Wei; Lim, Anita Y. N.; Teng, Gim Gee; Tay, Sen Hee
Abstract: Aims: Urate‐lowering therapy (ULT) is effective in gout, but suboptimal management with wide variability in dose escalation remains widespread. We protocolized dose escalation of ULT to improve gout management. The aim was to reduce time to achieve target serum urate (SU) <360 µmol/L. Methods: Process improvement tools were used to identify underlying causes of prolonged time to target SU. We designed a nurse‐led telemedicine intervention for dose escalation of ULT. Patients with gout with SU ≥360 µmol/L meeting indications for ULT at a single institution were recruited. Exclusion criteria were estimated glomerular filtration rate <30 mL/min, pregnancy, cognitive impairment and poor mobility. A nurse‐led telemedicine clinic was set up to perform patient education, monitoring of adverse events and drug escalation. We partnered with primary healthcare centers for routine blood tests. Results: From July 2016 to December 2017, 127 patients were recruited. Median time to target SU was 19.0 weeks (interquartile range [IQR] 11.0‐31.0). Median dose of allopurinol was 300 mg/d (IQR 200‐400) in normal renal function and lower in renal impairment. Median telemedicine calls required to achieve target SU was 2 (IQR 1‐3). No patient was hospitalized for gout flares. Two patients had adverse drug reactions, one required cessation of allopurinol for rash with eosinophilia, the other had self‐resolving ulcers and allopurinol was continued. Lower baseline SU and number of gout flares were associated with attainment of target SU. Conclusion: A nurse‐led telemedicine for gout care is effective and safe. Our results affirm the utility of telemedicine in increasing access to care and lower healthcare utilization.